Improving rice salt tolerance by precision breeding in a new era. (April 2021) - Ganie, Showkat Ahmad; Wani, Shabir Hussain; Henry, Robert; Hensel, Goetz
Abstract : Rice is a premier staple food that constitutes the bulk of the daily diet of the majority of people in Asia. Agricultural productivity must be boosted to support this huge demand for rice. However, production is jeopardized by soil salinity. Advances in whole-genome sequencing, marker-assisted breeding strategies, and targeted mutagenesis have substantially improved the toolbox of today's breeders. Given that salinity has a major influence on rice at both the seedling and reproductive stages, understanding and manipulating this trait will have an enormous impact on sustainable production. This article summarizes recent developments in the understanding of the mechanisms of salt tolerance and how state-of-the-art tools such as RNA guided CRISPR endonuclease technology including targeted mutagenesis or base and prime editing can help in gene discovery and functional analysis as well as in transferring favorable alleles into elite breeding material to speed the breeding of salt-tolerant rice cultivars.